Exploring the factors influencing resignation intentions among university lecturers: A case study in Vietnam - Le, Hau (Journal of Finance - Marketing Research, 2025)
Faculty resignation intention is a huge problem at public and private universities in the country, suffering from a shortage of qualified lecturers. This study contributes to the understanding of faculty turnover in Vietnamese universities by examining resignation intention among university lecturers in Vietnam: job pressure, job satisfaction, and organizational commitment. The present research will be grounded and expanded on Ajzen’s Theory of Planned Behavior, which explains how the above-mentioned factors add to faculty turnover and offers recommendations for universities to improve faculty retention and reduce turnover. A mixed-methods approach was adopted for the research method, combining qualitative semi-structured interviews and quantitative surveys to collect data from 303 university lecturers throughout various regions in Vietnam, providing both theoretical and practical insights into the retention of university faculty. The results showed that job pressure positively influenced resignation intention, while job satisfaction and organizational commitment negatively influenced the lecturer’s intention to resign. Most importantly, the study finds that work pressure is the most significant predictor of intention to resign; thus, universities must manage workload effectively to sustain academic talent, an area that has been underexplored in the Vietnamese context until now. This would, inversely, mean job pressure needs to be brought down and mitigated while increasing job satisfaction, which eventually reinforces organizational commitment. If turnover needs to be minimized, the improvement in faculty retention. These results bring empirical recommendations for university administrators regarding improving retention strategies to ensure stability and further development at Vietnamese higher education institutions.